ANALISIS YURIDIS NORMATIF DAN HUKUM ISLAM TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30- 74/PUU-XII/2014 TENTANG BATAS USIA PERKAWINAN ANAK (PEREMPUAN) ABDUL HADI DAN HASANAIN HAIKAL - Hasanain Haikal (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
Age criteria in marriage law which sets the age limit for 16 years women is disputed by the applicant judicial review to the Constitutional Court (MK) through case No. 30 and 74 / PUU-XII /2014 on Age Limits on Marriage Children (Women), then it must be raised to be 18 years old. The applicant considers  that the marriage law contrary to the Constitution (Constitution) 1945, which is "16 years phrase" in Article 7 contrary to the Constitution 1945. Applicant considers that early marriage is done when the child is not yet mature psychologically and biologically. On the other hand from the viewpoint of Islam, the Islamic jurists and religious leaders had other considerations, because in Islam knows no age limits. The Courtrejected the applicant's claim of judicial review, the Court assesses the applicant's argument is  groundless and rejected the applicant states in its entirety. The judge considers that the needs of the age limit for women especially adapted to many aspects, such as health, social, cultural, and economic. In fact, there is no guarantee limit increasemarriage age for women from 15 to 18 years would reduce the divorce rate, tackling health problems, as well as other social issues. To prevent child marriage that emergemany issues, the Court argues thatit is not only by the sheer age limit but also the various social aspects of economic development, culture, and technology.